Pengetahuan Ibu dan Asupan Zat Gizi Makro Berhubungan dengan Kejadian Gizi Kurang pada Anak Usia 12-24 Bulan - Eke Febriani; Anang Wahyudi; Miratul Haya (Poltekkes Kemenkes Jakarta III, 2019)
The nutritional fulfillment in childhood is an important period because this time is also known as the first thousand days of life divided into two important times, namely 270 days (9 months) in the womb and 730 days (2 years) after babies born to children Two years old. The purpose of this research is to know the relationship of maternal knowledge and nutrient intake of macro nutrients with the incidence of malnutrition in infants aged 12-24 months in the village Panorama of Bengkulu in 2019. The study uses analytical observational design with a case control approach. The technique used is Purposive Sampling with a sample number of 30 toddlers. The results of this study using Chi-Square test analysis showed that there is a relationship between mother knowledge and macro nutrient intake with less nutritional incidence with value (P-value ≤ 0.05). Maternal knowledge (P-value 0.014), energy (P-value 0.023), Protein (P-value 0.009), FAT (p-value 0.020), carbohydrates (p-value 0.027). This research advises people to pay more attention to the nutrient intake of macro nutrients for better child growth and development. As well as active in posyandu activities and nutritional consultation so that mothers get knowledge about nutrients needed for toddlers.